Chlamydia trachomatis infection among pelvic inflammatory disease patients attending the gynaecology clinic of a private tertiary hospital in Ogun State, Nigeria. (2024)
Background: Pelvic inflammatory disease (PID) is one of the very serious complications arising from sexually transmitted infections (STIs) and Chlamydia trachomatis has been implicated as one of the commonest causes of STI. Considering the adverse sequelae of PID, there is a need for locally relevant data which will guide preventive and therapeutic efforts. Detection of a combination of immunoglobulin G (IgG) and immunoglobulin A (IgA) has been described as an indicator of an actively chronic infection Aims: The aim of this study was to determine the prevalence of Chlamydia trachomatis infection by the use of IgA and IgG and evaluate the associated risk factors among females that presented with Pelvic inflammatory disease at the gynaecology clinic of Babcock University Teaching Hospital. Ilishan-Remo, Ogun State, Nigeria. (BUTH) Materials and Methods: This was a hospital–based, case-controlled study involving 44 patients diagnosed with PID and 44 age-matched controls at the gynaecology clinic of BUTHI. Interviewer-administered questionnaires were used to obtain information on socio-demographic characteristics, and risk factors for PID, from consenting participants. Blood samples were collected from each participant and analysed, using the enzyme-linked immunosorbent assay, for Chlamydia trachomatis type specific for IgA and IgG. Analysis was done by SPSS, IBM version 23.0 Results: Both IgG and IgA were present in 15 cases (34.1%) as compared to none of the controls. The difference between Chlamydia IgG, IgA and (IgG+IgA) among the cases and the controls were statistically significant. Majority of the participants positive for the immunoglobulins were aged 25 years or younger (11, 73.3%), number of lifetime sex partners and age of first sexual intercourse being 18 years or younger were statistically associated with Chlamydia trachomatis causing PID. Conclusion: Chlamydia trachomatis remains an important causative pathogen of PID and more prevalent among the young people. Screening is advocated among the young in resource limited countries.